Quranic View upon Political Bases of Prophet Muhammad in Facing with Ahlolketab (Followers of Moses and Jesuse (a.s)) - Gholam Hussain Arabi; Hasan Kazemi Nezhad (آموزه‌های قرآنی)
Prophet Muhammad's political treatment is based on important regular methods. Despite this importance disregarded .this research seeking for extracting political bases from prom its treatment with Ahlolketab. Because of this goal I've studied all verses in quran one by one, specially verses are related with Ahlolketab. The results of this research are mentioned below: a- peaceful life with them;b- inviting them to Islam and unity; c- avoid from making them nervous; d-bewaring them about their wrong treatment; e- jihad against them. It is qualify to mention that: all these bases are written in table form with quranic evidences.